Properties of kinetic Alfvén waves (KAWs) in negative-positive ion plasma of Titan’s ionosphere - Arooj, Shanza; Shan, Shaukat Ali; Saleem, Hamid (Astrophysics and space science, 2025)
The properties of kinetic Alfvén waves (KAWs) are investigated in the negative positive ion electron (NPIE) plasma of Titan’s ionosphere. The concentrations of positive and negative ions in dayside and nightside regions of this ionosphere are different, whereas the magnitude of the ambient magnetic field also varies. The plasma data indicate the possibility for the existence of very low frequency and long wavelength kinetic Alfvén waves (KAWs) in this environment. The frequencies and wavelengths of these waves are estimated considering only the two kinds of positive H C N H + and negative C N − ions, which have dominant concentrations. Extremely small magnetic field ∣ B 0 ∣ ≃ 0.0002 G can sustain KAWs with extremely small frequencies of the order of ≃ 0.004 rad / s and very long wavelengths of the order of a thousand kilometres along field lines while the Titan is about a million kilometres away from Saturn’s surface. It is pointed out that the weakly nonlinear KAWs can also give rise to electromagnetic solitary waves similar to the Earth’s upper ionosphere. The formation of solitary structures by the nonlinear KAWs is also investigated using the appropriate normalization of spatial coordinates in parallel and perpendicular directions with respect to the ambient magnetic field. The almost stationary electromagnetic pulses may appear in Titan’s ionosphere moving at very small speeds.